Objective methods for assessing the severity of patients condition in a surgical intensive care unit - F. A. Pchelintseva; M. V. Petrova; I. S. Shmyr; K. A. Mironov; E. V. Gameeva (Исследования и практика в медицине)
Purpose of the review. Analysis of the objective methods to evaluate the need for prognostic scalesin the intensive care unit for predicting the risk of complications and mortality of cancer patients after elective surgery. The review considers methods for an objective assessment of the severity of the condition of patients in the intensive care unit of the oncological surgical profile: prognostic scales and expert evaluations. We have analyzed studies of foreign and Russian experts about comparing the best of the different prognostic scales in clinical practice for post-elective surgical cancer patients.Conclusion. Our review considers the need for an objective value of the severity of patients on admission to the intensive care unit for elective oncological surgeries by using prognostic scales. Further researchand selection of the most effective prognostic score complying with the principles of evidence-based medicine for this group of patients have a goodprospect.